Zakat as Al-Harakah al-Jawhariyyah: Reconstruction of the Ontology of Islamic Education Based on Sadra's Metaphysics - Unang Sudarma; Awang Faisal Assyifa Ag Rahim; Iu Rusliana (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2025)
The general understanding of Islamic philanthropy, especially zakat, is often limited to its function of material redistribution, thereby neglecting its potential as a means of more fundamental educational transformation. This study aims to analyze the BEBEZA (Berdaya Bersama Zakat) Program in Sukabumi, one of Regencies in West Java, as an ontological manifestation of Islamic Religious Education in the process of strengthening mustahiq. This study attempts to connect philosophical discourse with empirical practice through an in-depth study of the transformation mechanisms that occur in mustahiq, which are understood not merely as economic empowerment, but as a process of enhancing self-quality existence. This study uses a qualitative approach with a case study design, and the analysis is conducted through the lens of Mulla Sadra's Ḥikmah Muta’āliyah, specifically the concepts of the principal of existence (Aṣālat al-Wujūd), the gradation of existence (Tashkīk al-Wujūd), and substantial movement (Al-Ḥarakah al-Jawhariyyah). Data was collected through in-depth interviews, participatory observation, and document study, then analyzed thematically and interpretively, accompanied by source triangulation to increase validity. The results show that the BEBEZA Program effectively triggers substantial movement in the mustahiq. The intervention not only has an impact on increasing economic capacity, but also improves the quality of their existence, which is reflected in the growth of self-confidence, initiative, social involvement, and spiritual deepening. This study concludes that a holistically designed Islamic philanthropy model can serve as a transformative educational instrument for shaping empowered and independent individuals (Insān al-Kāmil), as well as offering an alternative philosophical framework for the design of religious-based empowerment programs.